Sistem Peramalan Waktu Masak Fisiologis Benih Padi Menggunakan Double Exponential Smoothing - Najmi Nurus Shofi; Mochamat Bintoro; Aji Seto Arifianto (Jurnal Teknologi Informasi dan Terapan, 2022)
The success of the rice harvest is influenced by various factors, one of which is the selection of quality seeds. Good rice seeds are those obtained during physiological maturity where the moisture content in the seeds is not too low/high. The physiological cooking time of rice seeds can be done by calculating heat accumulation and testing germination. Heat accumulation is the total heat energy from solar radiation received by rice plants, this value can be calculated by recording the maximum, minimum, and humidity temperature data continuously for 90-120 days. Meanwhile, post-harvest laboratory tests were carried out for germination. Temperature and humidity data that were stored and processed quickly of course could be predicted the physiological ripening time of seeds better. Therefore in this article, a web-based forecasting system with the double exponential smoothing method was developed and supported by a graphical display of the data development. This research was conducted on 3 rice varieties namely IR64, Sinta Nur, and Ciherang. The yield that could be conveyed for the IR64 variety reached 85% germination with heat accumulation of 1147 and 105 DAS. The Sinta Nur variety had 92% germination and 86% Ciherang variety with heat accumulation of 1266 at 115 DAS. In this forecasting process, the MAPE value is 0.205 with alpha 0.9 and beta 0.1.